The unity of the common law - Brudner, Alan (Alan J.) (Oxford : Oxford University Press, 2014)
The structure of common law has for many years been the subject of intense debate between formalists and functionalists. The former, drawing on legal realism, proposes that transactional law is a private law for interacting parties, while the later inspired by Kant, argue it is a public law serving the collective ends of society. But what if there were a unity between functionalism and formalism? What if, in this unity private law is modfied by a common good? In this revised and re-written edition, Alan Brudner draws on Hegel's legal philosophy to exhibit this unity in each of transactional laws main divisions; property, contract, unjust enrichment and tort. Brudner suggests each of these divisions is composed of private-law and public-law parts that complement each other and that they are connected by a single narrative thread. This thread consists in development towards a goal.
Previous ed: 1995.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 5, 2013).
Keywords: Common law; Civil law; Law -- Philosophy; Law; Jurisprudence & general issues